THE INTRIGUING LIGAND-DEPENDENT AND LIGAND-INDEPENDENT ACTIONS OF THE GROWTH HORMONE SECRETAGOGUE RECEPTOR ON REWARD-RELATED BEHAVIORS. (January 2021) - Cornejo, María P.; Mustafá, Emilio R.; Barrile, Franco; Cassano, Daniela; De Francesco, Pablo N.; Raingo, Jesica; Perello, Mario
Highlights: GHSR displays ligand-dependent and ligand-independent actions. GHSR regulates the activity of the dopamine mesocorticolimbic pathway. GHSR enhances reward-related behaviors towards palatable stimuli and drugs of abuse. Abstract: The growth hormone secretagogue receptor (GHSR) is a G-protein-coupled receptor (GPCR) highly expressed in the brain, and also in some peripheral tissues. GHSR activity is evoked by the stomach-derived peptide hormone ghrelin and abrogated by the intestine-derived liver-expressed antimicrobial peptide 2 (LEAP2). In vitro, GHSR displays ligand-independent actions, including a high constitutive activity and an allosteric modulation of other GPCRs. Beyond its neuroendocrine and metabolic effects, cumulative evidence shows that GHSR regulates the activity of the mesocorticolimbic pathway and modulates complex reward-related behaviors towards different stimuli. Here, we review current evidence indicating that ligand-dependent and ligand-independent actions of GHSR enhance reward-related behaviors towards appetitive stimuli and drugs of abuse. We discuss putative neuronal networks and molecular mechanisms that GHSR would engage to modulate such reward-related behaviors. Finally, we briefly discuss imaging studies showing that ghrelin would also regulate reward processing in humans. Overall, we conclude that GHSR is a key regulator of the mesocorticolimbic pathway that influences its activity and, consequently, modulates reward-related behaviors via ligand-dependent and ligand-independent actions.